Physical and geotechnical properties of coal ash - Tony Kismoor, anak Sasak. (Universiti Malaysia Sarawak, UNIMAS, 2006)
The present thesis aimed at studying the physical and geotechnical properties of locally available coal ash. To accomplish this study, three types of coal ash; fly ash, pond ash and bottom ash have been collected from Sejingkat Thermal Plant, Kuching, Sarawak, Malaysia.